Ethics, supervenience and Ramsey sentences - Williamson, T (Wiley-Blackwell, 2001)
In "From Metaphysics to Ethics", Frank Jackson presents an impressively systematic conception of modal reality and its relation to our thought. His account of ethics is a test case for this conception. I will argue that Jackson's reasoning for his conclusions about ethics is unsound.